A novel simulation approach for particulate flows during filtration. Issue 4 (26th January 2021) - Qi, Minhui; Li, Mingzhong; Moghanloo, Rouzbeh G.; Guo, Tiankui
Abstract: This paper presents a novel approach for simulation of filtration process when velocity gradient within pore space cannot be neglected. The new model is useful for accurate prediction of the filtration performance and particle retention efficiency. Artificial porous media such as filters, by design, have a large surface‐to‐volume ratio because of an inherent homogeneity present within their structure; the homogenous structure is realized due to organized packing of grains as building blocks, which leads to a significant velocity gradient inner pore space. In this work, the inner‐pore flow characteristics of two different homogeneous packing patterns (cubic and oblique hexagonal packing) were examined. The multiple constricted tubes analogy was adopted to model porous media to simplify the inner‐pore geometrical structure. A new integrated simulation approach was utilized through implementing the particle trajectory model to every unit bed element of the simulation domain. The accuracy of the numerical simulations used in this study was verified by comparing the particle distribution pattern and penetration depth obtained from simulations to those monitored via a visual experiment. A sensitivity analysis was carried out to study parameters that may affect the particle distribution and penetration length, such as grain‐to‐particle size ratio, flow rate, and fluid viscosity. The simulation method utilized in this paper provides an in‐depth understanding of the fine particle migration during filtration process through artificial porous media, and, thus, provide useful insights for improved filtration design.